(untitled) (Journal of Forensic Medicine & Toxicology, 2014)
Estimation of age of a person, whether living or dead, is vexing problem for medical jurist.1The duty of Forensic medicine knowledge expert is not only to examine dead bodies but also to give his opinion in living individual for solving various medico-legal problems like determination of age, identification, sexual assault, sterility impotency, pregnancy, criminal abortion, disputed paternity, alcoholic intoxication etc. Skeletal age, dental age, morphological age, secondary sex character age are other method in use for asserting age of individual. In medico legal practice a combined view is taken and opinion is expressed after considering all methods. However radiological examination is a must and the court of law did not believe any conclusion without it. 2 The present study was conducted on Agra region population to study union of lower end of humerus for estimation of age.